Comparison of Recurrence after Ptrygium Excision with Amniotic Membrane Graft Verses Stem Cell Graft - Irfan Qayyum, Ayesha Hanif, Nukhba Zahid (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the recurrence of pterygium with amniotic membrane versus stem cell graft techniques after pterygium excision. Study Design: Randomized Controlled Trial. Place and Duration of Study: Study was conducted at DHQ Teaching Hospital, Gujranwala, for duration of 12 Months from July 2016 - June 2017. Material and Methods: This was a quasi experimental study where two surgical procedures were opted for pterygium excision. The patients were divided into two equal groups. One group had pterygium excision with stem cells grafting and the other group had pterygium excision with amniotic membrane grafting. Patients of both gender, above 18 years of age with grade 2-3 of pterygium causing discomfort, visual impairment or cosmetic disfigurement were included in the study. Whereas patients with id abnormalities, lacrimal sac infection, dry eye syndrome, pseudo pterygium and patients with recurrent epithelial erosions were excluded from the study Results: The mean age was 42 ? 9.3 years. There were 38 (63.3%) males and 22 (36.7%) were females in this study. Recurrence rate with amniotic membrane was 10 % and with stem cell graft was 3.3%. Conclusion: Stem cell grafting has less recurrence and better cosmetic appearance than amniotic membrane graft. Key words: Amniotic membrane graft, Pseudo pterygium, surgical procedures, stem cell graft.